ASR Automatic Speech Recognition for European Portuguese with the Kaldi Framework - M.Breternitz; Dias, J.; Pedro Santos (CIENCIA 2018 Encontro com a Ciencia e Tecnologia em Portugal, 2018)
Introduction  ASR – Automatic Speech Recognition  The Kaldi ASR Toolkit  European Portuguese ASR Development  Experimental Set UP, Results  Future Work